Methodological notes on composite indicators for monitoring working conditions - Andranik S. Tangian (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2018)
Several devices in designing composite indicators for policy monitoring and benchmarking are discussed: weighting and scaling of variables, hierarchical organization, handling rank-based variables, relief tables, survey simulation techniques which combine normative and empirical data. Some remarks are made on survey design to facilitate constructing composite indicators.
urn:nbn:de:swb:90-873542
Keywords: 330; composite indicators; methodology of policy monitoring and benchmarking; hierarchy of indices; scaling; rank-based variables; relief tables; survey design; working conditions